(untitled) (Cadernos de Letras da UFF, 2020)
In his play Endgame, Samuel Beckett explores individuals divided between the simplicity and the complexity of mind and body. Therefore, based on Ricoeur’s concepts of memory and body (1968; 2007), this article aims to analyze the knowledge from the self and the other in the play, and how dependent they are on each other and their memories.